2010
DOI: 10.1177/030089161009600113
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation of Pacemakers and Cardio-Defibrillators in Patients Submitted to Radiotherapy: A Clinical Experience

Abstract: Our study confirms the safety of radiotherapy for patients implanted with pacemakers or implantable cardioverter-defibrillators but suggests that chemoradiation represents a probable risk factor for cardiac toxicity. Furthermore, all cardiac events were observed in patients treated in the head and'neck or left thoracic areas. A standardized protocol is advisable in order to improve patient control during the radiotherapy treatment. It is mandatory to calculate the dose received at the pacemaker/heart, even in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
(63 reference statements)
0
25
0
1
Order By: Relevance
“…Ferrara et al reported no problems in a cohort of 45 patients with an average maximum CIED dose equal to 2.5 Gy for patients treated in the head & neck area and equal to 1.8 Gy for patients treated in the thoracic area [36]. Kapa et al reported on 12 patients treated between 2002 and 2007 [31].…”
Section: Methodsmentioning
confidence: 99%
“…Ferrara et al reported no problems in a cohort of 45 patients with an average maximum CIED dose equal to 2.5 Gy for patients treated in the head & neck area and equal to 1.8 Gy for patients treated in the thoracic area [36]. Kapa et al reported on 12 patients treated between 2002 and 2007 [31].…”
Section: Methodsmentioning
confidence: 99%
“…There can be complex interplay between the dose‐rate, the frequency of dose pulses, and the sensing band of a CIED. It is not known which time‐scale is most relevant for dose‐rate effects: dose per linear accelerator (LINAC) pulse (elevated in flattening filter free “FFF” beams), dose per second (elevated for higher nominal dose‐rates), dose per minute (elevated in volumetric modulated radiation therapy “VMAT”), or dose per fraction (elevated in stereotactic body radiation therapy “SBRT” or stereotactic radiosurgery “SRS”) …”
Section: Conditions In Clinical Use That Can Induce Malfunctionsmentioning
confidence: 99%
“…Cardiac devices may be affected in two ways; electromagnetic interference (EMI) and direct damage to the circuitry via ionising radiation, both of which may cause temporary and permanent device malfunction [3]. Changes within the device parameters as result of EMI are seen even when the CIED is placed outside the radiotherapy treatment field [7].…”
Section: Introductionmentioning
confidence: 99%